Mid and long-term overall survival after carcinologic resections of thyroid cancer bone metastases - Fragnaud, Henri; Mattei, Jean-Camille; Le Nail, Louis-Romée; Nguyễn, Mỹ-Vân; Schubert, Thomas; Griffin, Anthony; Wunder, Jay; Biau, David; Gouin, François; Bonnevialle, Paul; Vaz, Gualter; Ropars, Mickael; et al. (Frontiers in Surgery, 2022)
Background: Bone metastases in thyroid cancer impair the patient’s quality of life and prognosis. Interestingly, wide margins resection as the surgical treatment of bone metastases might improve the overall survival (OS). Nonetheless, data are lacking regarding the potential benefits of this strategy. Methods: In order to assess the OS of patients with thyroid cancer after a bone metastases carcinologic resection, a retrospective multicentric study was performed, evaluating the 1, 5, 10 and 15 years-OS along with the potential prognosis associated factors. Results: 40 patients have been included in this multicentric study, with a mean follow-up after surgery of 46.6 ± 58 months. We observed 25 (62.5%) unimestastatic patients and 15 multimetastatic patients (37.5%). The median overall survival after resection was 48 ± 57.3 months. OS at 1, 5, 10, and 15 years was respectively 76.2%, 63.6%, 63.6%, and 31.8%. Survival for patients with a single bone metastasis at 15 year was 82.3%, compared with 0.0% (Log Rank, p = 0.022) for multi-metastatic bone patients. Conclusions: This study advocates for an increased long term 10-year OS in patients with thyroid cancer, after resection of a single bone metastasis, suggesting the benefits of this strategy in this population.